The Significance of Indigenous Knowledge Systems (IKS) for Africa’s Socio-Cultural and Economic Development in the Dawn of the Fourth Industrial Revolution (4IR) - Tondi, Pakiso (Journal of Gender, Information and Development in Africa, 2019)
Considering the frictions and tensions about the socio-cultural and economic development of Africa and the existence of some of tendencies and actions that are not in favour of the continent’s advancement, the main aim of this article is to argue for the deliberate reinstatement and retrieval of African Indigenous Knowledge Systems (IKS). The purpose this argument which in the main is a political position of an African cultural activist is to motivate for the use of IKS as a tool for socio-cultural change and economic development strategies that are vital in the era of globalisation and the Fourth Industrial Revolution (4IR). This is not new in that as demonstrated by situations of Japan and other Asian countries, IKS has all the potential to enable the African continent to meet the challenges of globalisation and chart its future. In addition, the article argues that the deliberate re-centering of IKS has a potential of complementing the 4IR initiatives with sciences that are embedded in life and work of communities that are majority in the world and are still depended on the natural resources that are under threat of diminishing.
Published Article
Keywords: African Indigenous Knowledge Systems (IKS); Re-Centering; Revitalization; Socio-Cultural; Economic; Development; Fourth Industrial Revolution (4IR)